The Effectiveness Differences Between Watermelon (Citrullus lanatus) Extract 100% and Carbamide Peroxide Gel 10% in Tooth Whitening (ex vivo) - Any Setyawati; Syifa Nabila Farah Fauziah Nur (Indonesian Dental Association, 2020)
Introduction: Discoloration can be caused by intrinsic or extrinsic factors. One of the discoloration treatments is teeth whitening. Teeth whitening process usually uses chemicals such as hydrogen peroxide or carbamide peroxide which can cause side effects, namely gingival irritation. Previous research has found that malic acid in strawberries can whiten teeth. Watermelons contain greater malic acid than strawberries. Objective: To analyze the effectiveness of 100% watermelon (Citrullus lanatus) extract on teeth whitening. Methods: The study was a laboratory experimental study with a total of 15 anterior post-extraction teeth which were discolored using black tea, divided into 3 groups. Group 1 was immersed in 100% watermelon extract, group 2 was immersed in 10% carbamide peroxide as positive control and group 3 was immersed in sterile aquades as negative control, for 56 hours, measured using a shade guide and spectrophotometer. Data were analyzed using one way Anova. Results: The 100% watermelon extract was effective for teeth whitening. There was a significant difference between 100% watermelon extract compared to negative control (p < 0.05). However, there was also a significant difference between 100% watermelon extract, and 10% carbamide peroxide gel (p = 0.003). Conclusion: The watermelon extract has the ability as teeth whitening agent. However, further study is still needed to explore this result and determine the proper concentration for teeth whitening.